PREVALENCE OF ADVERSE DRUG REACTIONS AMONG HIV/AIDS PATIENTS ON HAART IN UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL (UMTH), NIGERIA: A FOUR-YEAR RETROSPECTIVE STUDY. (12th February 2017) - Bassi, Peter; Gashau, Wadzani; Olaf, Klungel; Dodoo, Alexander; Okonkwo, Prosper; Kanki, Phyllis
Abstract : Background: Current evidence on highly active antiretroviral therapy (HAART) indicates that each person will have to take the drugs for life [1]. Since 2000, the prevalence of HIV in Nigeria has shown a gradual consistent decline from 5.0% in 2003 to 4.1% in 2010 following the introduction of HAART. While HAART improves the quality of life among HIV patients, adverse drug reactions (ADRs) may compromise quality of life in some patients. Methods: We performed a retrospective study at HIV/AIDs clinic, UMTH Nigeria, among ART-naive adult patients recruited from January 2006 to December 2010 and followed up for 48 months from commencement of HAART. Database and clinical charts of eligible patients were extracted for clinical information, type of reported ADRs, and physician's decision on whether or not ADRs was serious according to ICH E2A guidelines. Data was analysed using SPSS Ver. 21. Logistic regression was used to calculate odds ratios and of ADR associated with patient and treatment characteristics. Results: Patients initiated on HAART (n=7260) were reviewed with a prevalence of serious ADRs (53.4%). Commonest ADRs were peripheral neuropathy (11.0%), itching (9.5%), anaemia (9.2%), dyspepsia (9.1%) skin rashes (9.1%), and various forms of dermatitis (5.5%). Almost all (96%) the reported ADRs occurred between 3–18 months of treatment. Patients initiating on a zidovudine and efavirenz-based regimen (p=0.015 and p=0.020 respectively), baseline CD4≤200/ mm3 (P=0.000), unemployed patients (P=0.000), students (p=0.000) and petty traders (p=0.000) were statistically significantly associated with increase occurrence of an ADR. Conclusions: The study has identified the prevalence, types and the determinants of ADRs among HIV/AIDs patients at UMTH, Nigeria. These findings might be helpful in developing clinical guidelines on ADRs profile as a major criterion for choosing HAART drugs, hence promoting pharmacovigilance of ARVs in Nigeria.